Coronavirus disease 2019 pneumonia with acute respiratory distress syndrome in a child requiring prolonged mechanical ventilation: A case report - Shraddha Sunthwal; Sagar Lad; Sanjay Bafna; Rajesh Kulkarni; Preeti Lad; Salma Ahmadi; Raj Ganacharya (Wolters Kluwer Medknow Publications, 2023)
Coronavirus disease 2019 (COVID-19) infection in children predominantly presents with milder symptoms and is apparently less severe. However, 2% of acute pediatric COVID-19 cases possessed severe manifestations. Here, we describe a case study of a 4-year-old boy suffering from acute COVID-19 infection that presented like an adult ARDS requiring prolonged ventilation and medical course complicated with hospital-acquired infection and thrombosis which is very rarely seen. After 45 days of mechanical ventilation, the child was successfully weaned off from ventilatory support. Notably, analysis of the current literature revealed that this represents the longest reported hospitalization and ventilation period for a child presenting with COVID-19 pneumonia with potential complications. It highlights the importance of allowing sufficient time for clinical interventions to take effect, even when the prognosis appears poor. Hence, treating physicians should be aware of this atypical presentation.